A virus based vaccine combined with IL12 gene therapy eradicates aggressive melanoma - Nuša Brišar; Katja Šuster; Simona Kranjc Brezar; Andrej Cör (Scientific Reports)
Abstract Our study introduces a novel bacteriophage-based vaccine strategy and evaluates its antitumor efficacy, both as a standalone therapy and in combination with gene electrotransfer (GET) of interleukin-12 (IL-12) plasmids. Using phage display technology, we produced engineered M13 bacteriophages expressing tumour peptides MAGE-A1, gp100, or MART-1/MELAN-A on the surface of the capsid. The therapeutic potential of bacteriophage vaccination alone or in combination with GET IL-12 was tested in vivo in a mouse malignant melanoma model. Response to treatment was further characterized by histological and immunohistochemical analyses of tumour tissue. No negative side effects were observed during treatment in mice. Engineered bacteriophage therapy significantly delayed tumour growth. GET IL-12 contributed to the therapeutic effect of engineered bacteriophages and increased tumour growth delay. Both therapies had a synergistic effect and led to complete responses in 30% of cases. Histological and immunohistochemical analyses have shown that both bacteriophage monotherapy and, especially in combination with GET IL-12, activate the immune system and increase the proportion of necrosis and the infiltration of macrophages, CD4 + and CD8 + T lymphocytes in tumours. For the first time, a cocktail of three engineered M13 bacteriophages displaying different melanoma-associated antigens with intratumoral IL-12 gene electrotransfer were applied, demonstrating a synergistic therapeutic effect in a highly aggressive melanoma model. Nanotechnological approaches, such as the use of genetically engineered bacteriophages, offer promising new avenues for the development of anti-tumour vaccines.